If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 9m = 9m + -3 Combine like terms: 5m + 9m = 14m 14m = 9m + -3 Reorder the terms: 14m = -3 + 9m Solving 14m = -3 + 9m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9m' to each side of the equation. 14m + -9m = -3 + 9m + -9m Combine like terms: 14m + -9m = 5m 5m = -3 + 9m + -9m Combine like terms: 9m + -9m = 0 5m = -3 + 0 5m = -3 Divide each side by '5'. m = -0.6 Simplifying m = -0.6
| p+c+m=1063 | | 8x+5=68 | | x+.4=2x+1.4 | | 25x^2-10x=4 | | 15x-2=40x+13 | | 12*x/4-x/13=-34 | | 5y-6+y+22=7y+20-3y | | -6(2p+3)-36=3(3p+3) | | 2t^2=9t | | 3(c-2)=4(c-8) | | -50+5y+5=3(4y-3)-8 | | 3(c-4)+5=2+c-9 | | 14(4x-2)=3x-6 | | 4-4x=10+2x | | 7-(-y-5)=2(y+3)-6(y+3) | | x+x+475000=625000000 | | (3+5x)(2-3x)=12-15x^2 | | -2(-3x+5)+6=4(x-2) | | (3xy-5y^2)(-4x)= | | s+w+2=304 | | (13w+10)-(2w+6)= | | w+s=304 | | 8(w-5)=-40 | | (3x+6)(6x-3)=0 | | 2x^2+12x+8=0 | | 6-3t=3t | | X^2+86x=0 | | (1-7xy+5x^2-y^2)-(6y^2-7xy-6)= | | -(8y+3)-(-7y-6)=-3 | | x^2-8x+5=y | | x^2-8x+5=x | | -(8y+3)-(7y-6)=-3 |